Postage stamp from Monaco commemorating science and the 25th anniversary of UNESCO - Claude Jumelet (1971)
Stamp depicts an alchemist, rocket, and radar system.
Keywords: Postage stamps; Radar; Unesco; Rockets (Aeronautics); Alchemists; Commemorative postage stamps; Science on postage stamps; Monaco